1999
DOI: 10.1007/s00585-999-1095-0
|View full text |Cite
|
Sign up to set email alerts
|

Meso-scale effects of tropical deforestation in Amazonia: preparatory LBA modelling studies

Abstract: Abstract. As part of the preparation for the Large-Scale Biosphere Atmosphere Experiment in Amazonia, a meso-scale modelling study was executed to highlight de®ciencies in the current understanding of land surface atmosphere interaction at local to sub-continental scales in the dry season. Meso-scale models were run in 1-D and 3-D mode for the area of Rondonia State, Brazil. The important conclusions are that without calibration it is dicult to model the energy partitioning of pasture; modelling that of forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Still, both timing and depth of the CBL seems to have been significantly underestimated over pasture, when compared with observations made concurrently at the same sites , arguably due to the inability of one-dimensional models to reproduce the thermal instabilities induced across the surrounding deforested strips. Similar results were encountered by Dolman et al (1999), who noted that modeling CBL over pastures in Rondônia may not only make it seem lower than observations (Calvet et al, 1997) but also colder and wetter, indicating the failure of SCMs to generate the necessary amount of heat to induce a deeper and warmer CBL. These findings were supported by additional experiments performed by Dolman et al (1999), who showed that even mesoscale gridded models may fail to properly predict both depth and temperature of the CBL over pastures in Rondônia, despite their ability to simulate the Tennekes (1973).…”
Section: Single-column Models (Scms)supporting
confidence: 80%
See 1 more Smart Citation
“…Still, both timing and depth of the CBL seems to have been significantly underestimated over pasture, when compared with observations made concurrently at the same sites , arguably due to the inability of one-dimensional models to reproduce the thermal instabilities induced across the surrounding deforested strips. Similar results were encountered by Dolman et al (1999), who noted that modeling CBL over pastures in Rondônia may not only make it seem lower than observations (Calvet et al, 1997) but also colder and wetter, indicating the failure of SCMs to generate the necessary amount of heat to induce a deeper and warmer CBL. These findings were supported by additional experiments performed by Dolman et al (1999), who showed that even mesoscale gridded models may fail to properly predict both depth and temperature of the CBL over pastures in Rondônia, despite their ability to simulate the Tennekes (1973).…”
Section: Single-column Models (Scms)supporting
confidence: 80%
“…Atmospheric instabilities induced between areas of forest and pasture (Dolman et al, 1999;Liu et al, 1999;Baidya Roy and Avissar, 2000;Souza et al, 2000;Weaver and Avissar, 2001) are thus better represented by mesoscale models, which have showed that the impact of such instabilities are (typically) quite different from the results encountered by AGCM simulations of a basin-wide deforestation (Table II).…”
Section: Mesoscale Modelsmentioning
confidence: 99%
“…In recent years, a variety of LBA results have been published. Available data range from those related to the mesoscale effects of tropical deforestation [ Dolman et al , 1999] to those describing biosphere‐atmosphere interactions, interactions among cloud and rain processes [ Silva Dias et al , 2002a], aerosol‐cloud interactions [ Andreae et al , 2004] and the transport of biomass burning emissions [ Freitas et al , 2006]. Specific data used in the numerical simulations were CCN concentrations and shape parameters of gamma functions representing cloud droplet spectra, as described by Martins et al [2004] and Gonçalves et al [2008].…”
Section: Introductionmentioning
confidence: 99%
“…These studies focused on the exchange of heat, water vapor, CO 2 , and other trace gases between the primary forest and the atmosphere (e.g., Fitzjarrald et al , 1990; Fitzjarrald & Moore, 1990; Wofsy et al , 1990). Determining the consequences of Amazon deforestation has been the focus of many numerical model studies (Nobre et al , 1991; Lean & Rowntree, 1993; Dolman et al , 1999). Observational studies specifically aimed to determine the impact of deforestation on climate and carbon exchange in the Amazon include the ABRACOS project (Anglo‐Brazilian Amazonian Climate Observation Study; Shuttleworth et al , 1991; Fisch, 1996; Gash et al , 1996) and LBA (Large‐Scale Biosphere–Atmosphere Experiment in Amazonia) field experiments.…”
Section: Introductionmentioning
confidence: 99%